Listening strategies and problems in comprehending English lecturers - Siaw,, Yuan Yii. (Universiti Malaysia Sarawak, UNIMAS, 2008)
Listening is a critical element in the competent language performance of adult second language learners, whether they are communicating at school, at work, or in the community. Therefore, the purpose of this study is to investigate on the use o f strategies in facilitating listening comprehension of lectures conducted in English among education undergraduates in UNIMAS, and problems that hinders these undergraduates’ comprehension when listening to lectures conducted in English. The participants for this study are one - hundred forty - nine ESL and TESL students. Questionnaires and semi - structured interviews were the two instruments employed in this study. The findings revealed that the most frequently employed strategies by these participants to faci litate their lecture comprehension are selective attention, note - taking, resourcing, inferencing, monitoring, and self - management strategies. Meanwhile, the exploration on the difficulties or barriers confronted by these participants reveals that they fre quently encounter problems in relation to their personal, visual support and physical setting factor. The findings imply that the awareness of the listening strategies frequently employed and factors that affect listening enable the education personnel to assist the adult ESL learners to develop a better listening comprehension of lectures conducted in English in the future.